The new lexical prefix in the Ukraine word-formative system (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The meaning and the word-formative structure of new words with the lexical prefix нано- created in the sphere of natural sciences and spread in other spheres owing to linguistic and extralinguistic factors are considered. The appearance and the development of the new morpheme with quantitative semantic are followed up, globalizing tendencies in its use are detected.
Keywords: lexical prefix; derivative word; terminological vocabulary; derivative means